Infections Acquired from Animals Other Than Pets - Shapiro, Daniel S. (Infectious Diseases, 2017)
• Half of the estimated 1500 human infectious diseases are zoonotic in origin. • As many zoonotic agents are uncommon in humans and, for a number, have been established as causes of laboratory-acquired infections, good communication with the clinical microbiology laboratory is essential. • Although the number of infectious agents potentially transmissible from a specific animal to humans may be great, many of these infections are limited geographically and need not be considered unless a bioterrorist event or the introduction of an infection to a new area is a possibility. • Bats are reservoirs for such emerging diseases as those caused by Nipah virus, Australian bat lyssavirus, the SARS coronavirus, and Ebola virus. While there are more rodent species than there are bat species, bats host more viral zoonoses per species than do rodents. • The majority of potential agents of bioterrorism are zoonotic.